Problem-solving coping and social support as mediators of academic stress and suicidal ideation among Malaysian and Indian adolescents - Khan, Aqeel (Springer New York LLC, 2016)
This study examined whether productive coping styles and social support were significant mediators of the relationship between academic stress and suicidal ideation. The survey was performed on a sample of 300 Malaysian and 300 Indian college students. The participants completed psychological assessments of productive coping styles, social support, academic stress, and suicidal ideation. Significant cultural and demographic differences emerged. Indian students reported higher suicidal ideation and academic stress than did Malaysian students, and Malaysian students received more social support and had better problem-solving coping styles than did Indian students. Overall, students who were male, non-religious, and from low-income families reported more academic stress and more suicidal ideation. Productive coping styles and overall social support strongly affected the relationship between academic stress and suicidal ideation among both countries’ participants.